Mediators and moderators of the relationship between body image and community integration among burn survivors. Issue 4 (June 2022) - Mercado, Amelia E.; Donthula, Deepanjli; Thomas, Jacob E.; Ring, David; Trust, Marc; Crijns, Tom J.
Highlights: Stigma accounts for the relationship between body image and community integration. Symptoms of posttraumatic stress disorder also account for this relationship. Posttraumatic growth did not moderate or mediate this relationship. Burn recovery should aim to reduce symptoms of distress and experienced stigma. Abstract: Introduction: Due to medical advances, care for patients that experience burns has shifted from saving life to improving quality of life. Reintegrating into the community and maintain body image satisfaction may be difficult after a severe burn. Several studies have analyzed these two variables independently, but none have addressed a potential interrelationship. Aim: To investigate the indirect or direct relationship of body image and community integration, potentially mediated or moderated by social stigma, symptoms of depression, symptoms of post-traumatic stress disorder (PTSD), or posttraumatic growth. Methods: Data from the Burn Models Systems (BMS) Database between the years 2014 and 2020, patients who were at least 18 years of age and who had completed questionnaires that measured body image satisfaction, attitudes of community integration, perceived social stigma, and symptoms of depression, symptoms of PTSD, and posttraumatic growth were used to analyze potential mediators and moderators of the relationship between body image and community integration using multivariable linear regression models and structural equation modeling. Results: Social stigma, symptoms of depression, and symptoms of PTSD were determined to completely mediate the association of body image and community integration. Posttraumatic growth did not mediate this association. Social stigma, symptoms of depression, symptoms of PTSD, and posttraumatic growth did not moderate the relationship between body image and community integration. Conclusion: The finding that symptoms of distress and social stigma account for the relationship between body image satisfaction and community integration support the potential for interventions that ameliorate distress to improve community integration and quality of life in people recovering from burn injuries.